Tantangan Etiket Digital dalam Pembentukan Kewarganegaraan Digital: Sebuah Systematic Literature Review pada Generasi Muda - Cendana Tricia Januaristy Gultom; Iqbal Arpannudin; Ardira Bunga Pramesty (Universitas Negeri Semarang, 2026)
The rapid development of digital technology has significantly transformed the lives of young people, particularly in how they interact, learn, and construct their sense of citizenship. This condition requires a deeper understanding of digital ethics as an essential component of modern citizenship education, especially within the context of school-based civic education, which plays a strategic role in shaping students’ character. This study aims to examine the role of digital ethics in supporting the character development of young people through citizenship education implemented in schools. The method employed is a Systematic Literature Review (SLR) following the PRISMA protocol to ensure transparency and accuracy in the literature selection process. The search was conducted through the Scopus database, resulting in 42 selected articles that were analyzed using VOSviewer to map key themes and conceptual relationships. The findings show that digital ethics is a crucial component of digital citizenship, contributing to the prevention of deviant behaviors such as cyberbullying, hate speech, and the dissemination of fake news. Furthermore, digital ethics fosters critical thinking, empathy, and social responsibility among students in digital environments. This study contributes by proposing a conceptual framework that highlights the importance of synergy between digital ethics and school-based citizenship education to develop a generation that is intelligent, critical, and ethical both online and offline.